Pelatihan Teknik Public Speaking bagi Santri Pondok Darul Amanah sebagai Upaya Penyiapan Kader Penceramah yang Kompeten - Syakirunni'am, Luqman; Ramadan, Deandra Kurnia; Al-Kasyaf, Muhammad Zheeva (Dharmahita: Journal of Community Service and Development, 2026)
Public speaking skills training is a strategic necessity for preparing students to become competent preachers adaptable to the dynamics of contemporary da’wah. This community service activity aims to improve the public speaking skills of students at Pondok Darul Amanah through a participatory-educational approach that emphasizes a balance between theoretical knowledge and practical skills. The training is conducted over four weeks, with intermediate and advanced students as the main participants. The community service methods include initial needs mapping, delivery of theoretical material on effective communication principles, vocal techniques, body language, and speech preparation, as well as speaking practice through simulations and direct feedback. Data collection was carried out through participatory observation, reflective questionnaires, limited interviews, and activity documentation. The data was analyzed descriptively and qualitatively, combined with simple quantitative analysis to see changes in the students’ competencies before and after the training. The results of the activity showed an increase in self-confidence, mastery of speech structure, use of intonation and body language, and students’ readiness to perform as speakers. Students also showed a positive change in their perception of public speaking and increased participation during the training process. This training made a real contribution to students’ empowerment and has the potential to become a model for sustainable capacity-building in public speaking within Islamic boarding schools.